Diagnostic accuracy of salivary biomarkers in alzheimer’s disease: A systematic review - Majeed, Amir A; Al-Anee, Auday M; Al-Rawi, Natheer H (Journal of Baghdad College of Dentistry, 2025)
Background: Alzheimer’s disease causes cognitive decline and neuronal death due to amyloid-beta plaques and neurofibrillary tangles. Current diagnostic methods are intrusive, expensive, and few, but early diagnosis improves patient outcomes. Due to its oral-brain axis relationship to the central nervous system, saliva may be a viable source of non-invasive Alzheimer’s biomarkers. This systematic review aimed to assess the diagnostic potential of salivary biomarkers for Alzheimer’s disease by carefully reviewing the existing data. Methodology: Studies published between January 1, 2008, and September 30, 2023, were the subject of a thorough literature search in the PubMed, Scopus, and Web of Science databases. Relevant data were extracted after studies were evaluated according to predetermined inclusion and exclusion criteria. The Oxford Centre for Evidence-Based Medicine criteria were implemented to evaluate the quality of the studies that were incorporated. Results: A total of 36 studies were included in the systematic review, as they met the inclusion criteria. Alzheimer’s disease patients exhibited significantly elevated salivary levels of beta-amyloid- 42 and p-tau in comparison to healthy controls. Patients with Alzheimer’s disease exhibited non-significant trends in salivary t-tau and lactoferrin. Conclusion: The levels of beta-amyloid-42 and p-tau in the saliva of patients with Alzheimer’s disease are significantly altered. Beta-amyloid-42 regard as a best marker in early diagnosis by salivary sample. These findings emphasize the prospect of saliva as a non-invasive source of biomarkers for the diagnosis of Alzheimer’s disease. Nevertheless, salivary tests must undergo additional validation in larger, well-characterized cohorts and standardization of methodologies before they can be implemented in clinical practice.